Spectrophotometric Study of Kinetics of Oxidation of Oximes of 3,5-Dimethyl-2,6-diarylpiperidin-4-ones with Quinolinium Fluorochromate - Vimala, T.; Jani Bai, T.S. (Asian Journal of Chemistry, 2010)
The rate of oxidation of 3,5-dimethyl-2,6-diarylpiperidin-4-one oximes with quinolinium fluorochromate (QFC) was followed in aqueous acetic acid medium. The influence of substrate, oxidant, H+ ions, ionic strength and dielectric constant on the reaction rates at varied temperature has been studied. The stoichiometry is 1:1 and the product of oxidation is the corresponding ketone. Activation parameters have been computed and a suitable mechanism has been suggested.